Aftermaths of the dawn of experience: on the impact of Ankersmit's sublime historical experience - Menezes, Jonathan [UNESP] (Routledge Journals, Taylor & Francis Ltd, 2018)
Historical experience is one of the most important topics of Frank Ankersmit's work. As we shall see in this article, historical experience' in the Ankersmitean sense is a rare and complex kind of experience, entirely different from the experiences we have in our daily lives, because it presupposes that a historian can be in direct contact with a past that is long gone. But can we really experience the past? How could a historian perform this? As Ankersmit has admitted, this impractical and unusual choice of experience as one of his theoretical guides is controversial, to say the least, especially among scholars strongly oriented by the linguistic turn, narrativism, postmodernism, and so on, because he claims that experience should have priority over language. In this article, the aim is to investigate some of the effects or the aftermaths of what I term the dawn of experience' in current theory and philosophy of history. The aim is also to question whether this dawn of experience necessarily means banishing language or representation. In my view, it does not, and experience presupposes a suspension of language, not a complete abandonment of it.
Keywords: Historical experience; historical representation; Ankersmit; Huizinga; narrativism; dissociation; suspension of language